A participação do público no telejornalismo : uma análise de programas regionais no Brasil - Dihl, bibiana Meneghini (2020)
This master thesis investigates the public participation in five regional TV newscasts broadcasted by TV stations connected to Rede Globo in different regions in Brazil. After analyzing ten episodes of the newscasts, it is possible to create a list of participation types, which are differentiated according to the effect and the change they have in the programs. The study takes into account the format and the content of the messages sent to the newscasts. This work also aims to identify if the participation happens in a simulated way, based on the concept created by Scolari (2008, 2014, 2018). This master thesis’s methodology is Content Analysis, by Bardin (1977). The newscasts are classified into two categories, which allow the identification of which formats and contents encourage the public to send more messages and enable the creation of a list of six types of participation. It is concluded that the public has a voice and changes the topics addressed by the program, although part of this communication is simulated.